LOBECTOMY A LIFELINE FOR CONGENITAL LOBAR EMPHYSEMA. A TWO DECADES EXPERIENCE OF A TEACHING HOSPITAL. : J Peop Univ Med Health Sci. 2025:15(3), 93-100. http://doi.org/10.46536/jpumhs/2025/15.03.663 - Muhammad Kaleem Ullah1, Muhammad Sami Ullah2, Mansoor Ali3, Ayesha Tariq4, Hassaan Raza5 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Respiratory complications in children are a severe clinical issue that will tend to develop early in life and, in most instances, will require surgical interventions. The symptomatology, the lobar involvement, and the consequences of the postoperative aspect are also important to understand to improve the management strategies. OBJECTIVE: The aim of the study was to assess the clinical presentation, lobar involvement, outcome of surgery and complications in patients who had respiratory conditions, and whose course was managed in early childhood. METHODS: The present retrospective study focuses on the pediatric CLE patients who have already undergone lobectomy in the Nishtar Medical University Hospital during the period 2005 to 2024. Demographic data, clinical history, surgical complications and outcome data were obtained. Each of them had a standard posterolateral thoracotomy. The data were analyzed using SPSS 27 with chi-square, where p 0.05 was taken to be significant. RESULTS: There were 68 patients, 90% of the patients were introduced before six months old, and 60.3% were male. The most common one was the left upper lobe (37 cases), then the right middle lobe (16 cases), and the right upper lobe (9 cases). In 66.2 % of cases, histopathology showed a deficiency of bronchial cartilage. There was no reported intraoperative mortality. The number of postoperative complications was low, with atelectasis (7.4%) and wound infection (4.4%) being the most prevalent ones. The vast majority of patients (85.3%) were cured without any complications, and the average hospitalization was 7.6 +-2.1 days. CONCLUSION: Early presentation and favorable surgical outcomes emphasize the importance of timely intervention, effective postoperative care, and continued research on risk factors influencing complications.